Is clinical stage T2c prostate cancer an intermediate‐ or high‐risk disease?. Issue 9 (9th December 2014) - Klaassen, Zachary; Singh, Abhay A.; Howard, Lauren E.; Feng, Zhaoyong; Trock, Bruce; Terris, Martha K.; Aronson, William J.; Cooperberg, Matthew R.; Amling, Christopher L.; Kane, Christopher J.; Partin, Alan; Han, Misop; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Clinical stage T2c (cT2c) is an indeterminate factor in prostate cancer (PC) risk stratification. According to the D'Amico grouping and American Urological Association guidelines, cT2c is a high risk, whereas the National Comprehensive Cancer Network and the European Urological Association classify cT2c as an intermediate risk. This study assessed whether cT2c tumors without other high‐risk factors (clinical stage T2c, not otherwise specified [cT2c‐NOS]) behaved as an intermediate or high risk through an analysis of biochemical recurrence (BCR) after radical prostatectomy. METHODS Two thousand seven hundred fifty‐nine men from the Shared Equal Access Regional Cancer Hospital (SEARCH) Database and 12, 900 men from Johns Hopkins Hospital (JHH) from 1988‐2011 and 1982‐2012, respectively, were analyzed. Patients were grouped into low‐risk (prostate‐specific antigen [PSA] < 10 ng/mL, Gleason sum ≤ 6, and cT1‐T2a), intermediate‐risk (PSA = 10‐20 ng/mL, Gleason sum = 7, or cT2b), and high‐risk PC categories (PSA > 20 ng/mL, Gleason sum = 8‐10, or cT3). Men with cT2c tumors who were not otherwise at high risk (ie, PSA< 20 ng/mL and Gleason sum < 8) were placed into a separate category termed cT2c‐NOS. Associations between cT2c‐NOS and intermediate‐ and high‐risk patients and BCR were tested with the log‐rank test and Cox proportional analysis models. RESULTS Ninety‐nine men (4%) from SEARCH and 202 men (2%) from JHH had tumors classified as cT2c‐NOS. The cT2c‐NOS patients had a BCR risk similar to that of the intermediate‐risk patients (SEARCH, P = .27; JHH, P = .23) but a significantly lower BCR risk in comparison with the high‐risk patients (SEARCH, P < .001; JHH, P < .001). When they were specifically compared with intermediate‐ and high‐risk patients, after adjustments for year and center, cT2c‐NOS patients had outcomes comparable to those of intermediate‐risk patients (SEARCH, P = .53; JHH, P = .54) but significantly better than those of high‐risk patients (SEARCH, P = .003; JHH, P < .001). CONCLUSIONS Patients with cT2c disease without other high‐risk features had outcomes similar to the outcomes of patients with intermediate‐risk PC and significantly better than the outcomes of patients with high‐risk PC. These findings suggest that men with cT2c disease should be considered to be at intermediate risk. Cancer 2015;121:1414–1421. © 2014 American Cancer Society.